An Examination of the P Requirements of Broiler Breeders for Performance, Progeny Quality and P Balance 1. Non-phytate Phosphorus - Ekmay, R.D.; Coon , C.N. (International Journal of Poultry Science, 2010)
A 40-wk study was performed to assess the effects of reduced dietary Non-Phytate Phosphorus (NPP) on broiler breeder performance, progeny quality and P balance. Seven hundred Cobb 500 chicks were reared according to Cobb guidelines (Cobb-Vantress, 2005) and transferred to a production house at 21 wk. At 24 wk, 285 birds were switched over to one of five experimental diets (5 groups of 57) that differed only in NPP. Phosphorus levels ranged from 0.2% to 0.4% NPP in 0.05% increments; and corresponded to a daily intake of 288, 360, 432, 504 and 576 mg at peak. Production performance, egg quality, breeder and progeny skeletal quality, hatchability, progeny weight and P retention were monitored throughout the experimental period. Results show that total egg production, egg number, age at sexual maturity and egg weight were not negatively effected by lowering NPP levels to 0.20% (288 mg/day). Shell quality, though statistically impacted by NPP level, remained at high levels for all treatments (above 1.081). Reproductively, reduced dietary NPP did not negatively impact hatchability or subsequent progeny performance. Day old progeny wt and progeny bone quality were not significantly different from the breeders fed different NPP intake. Breeder tibia ash and relative strength was impaired at 0.20% NPP. The % total P (TP) retention showed a negative linear response with increasing dietary NPP, although absolute P retained increased with increasing dietary NPP. The amount of P deposited into the egg was not different among the treatment groups. Results appear to indicate that 360 mg NPP/day at peak (0.25% NPP) is sufficient for breeder hen performance, progeny 1 d wt and progeny skeletal quality. Breeder hens are able to maintain their performance by mobilizing bone reserves to meet the demands of egg formation and utilize dietary sources to replenish these reserves.